Koperasi Kakitangan Kerajaan & Badan - Badan Berkanun (Kokanun) Berhad / Norsyakirah Azra A. Wahad - A.Wahad, Norsyakirah Azra (Faculty of Business and Management, 2023)
This piece of writing was composed with the intention to summarise and for a recap of my six months of my employment entitled as an internship or practical workers. All the memories and all the roller coaster emotions expressed in this write up. The contents started from my updated profile followed by company’s profile, my training experience, the SWOT analysis, discussion, recommendations, conclusion and closed with the appendices.